Assessing Quality of Life in Patients with Epidermolysis Bullosa in the Saudi Population: Validation of the QOLEB Questionnaire - Shehata N; Mahmoud SA; Abdulghani S; Alghamdi Y; Awan ZA; Alshahrani NZ; Algethami MR; Bamimore MA (Clinical, Cosmetic and Investigational Dermatology)
Nancy Shehata,1 Saifaleslam A Mahmoud,2 Sultana Abdulghani,1 Yara Alghamdi,1 Zuhier A Awan,3 Najim Z Alshahrani,4 Mohammed R Algethami,4 Mary A Bamimore5,6 1Department of Dermatology, King Abdullah Medical Complex, Jeddah, Saudi Arabia; 2Department of Medicine and Surgery, Batterjee Medical College, Aseer, Saudi Arabia; 3Department of Clinical Biochemistry, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 4Department of Family Medicine, Faculty of Medicine, University of Jeddah, Jeddah, Saudi Arabia; 5Faculty of Public Health, Department of Nutrition, University of Ibadan, Ibadan, Nigeria; 6Lawrence Kinlin School of Business, London South Campus, Fanshawe College, London, ON, CanadaCorrespondence: Nancy Shehata, Department of Dermatology, King Abdullah Medical Complex, Jeddah, Saudi Arabia, Tel +966504499894, Email nancyshehata@gmail.comBackground: Epidermolysis bullosa (EB) is a rare condition where skin easily blisters. Using an Arabic-translated Quality of Life in Epidermolysis bullosa (QOLEB) questionnaire, we evaluated quality of life across persons with EB in Kingdom of Saudi Arabia.Methods: Respondents were selected through nonprobability convenience sampling. Data were collected using a pre-validated questionnaire. We statistically compared response data across the four EB phenotypes using the Kruskal–Wallis test. Validity was assessed through confirmatory factor analysis and Cronbach’s alpha was used to evaluate reliability with results 0.88.Results: The study included 91 participants with Epidermolysis Bullosa (EB), comprising 60.4% of them were males. Adults and adolescents constituted 61.5% of the study sample. Children with EB faced more bathing challenges, with 64.3% always needing assistance compared to 31.4% of adults/adolescents. Writing adaptations varied significantly (p=0.03), with children exploring alternatives like typing, while adults primarily struggled to hold a pen.Conclusion: Our findings underscore the profound physical, psychological, and social burdens associated with this rare condition, emphasizing the critical need for multidisciplinary care approaches. Addressing gaps in public awareness, improving access to specialized care, and providing psychosocial support for patients and their families are essential steps toward enhancing quality of life.Keywords: epidermolysis bullosa, quality of life, questionnaire, Saudi Arabia